Experience, Analogy and Mechanism in Maupertuis’s Theory of Generation - Storni, Marco (Cham: Springer, 2022)
At the mid-eighteenth century, the formulation of alternative theories undermined the hegemony of preexistence in the debate on animal generation. The new theories were characterized by a revival of epigenesis, and by a naturalization of the explanatory models. A key text in the mid-century renaissance of epigenesis is Pierre-Louis Moreau de Maupertuis’s "Vénus physique" (1745). While interpreters have unanimously acknowledged the role of this text in changing the course of the debate, the reasons for Maupertuis’s originality have not been studied in depth. Also, the relationship between the "Vénus physique" and the mechanistic view of generation is not entirely clear. With respect to the first point, I argue that Maupertuis is original in the theoretical framework he develops. He adopts a strongly empiricist stance and is skeptical about the possibility of the human intellect attaining a reliable knowledge of nature. As for the second point, I show not only that the reference to mechanism, and to Descartes’s work, is important in defining the terms of the controversy over preexistence. The appropriation of the mechanistic view, its updating, and eventual dismissal, are also important passages in the constitution of Enlightenment embryology, fostering the rise of a materialist approach in the 1750s.